Horizontal Basal Cells Are Multipotent Progenitors in Normal and Injured Adult Olfactory Epithelium - Iwai, Naomi (2008)
The mammalian olfactory neuroepithelium provides a unique system for understanding the regulation of neurogenesis by adult neural stem cells. Recently, mouse horizontal basal cells (HBCs) were identified as stem cells that regenerate olfactory receptor neurons (ORNs) and non-neuronal cell types only after extensive injury of the olfactory epithelium (OE). Here we report a broader spectrum of action for these cells. We show that even during normal neuronal turnover, HBCs actively generate neuronal and non-neuronal cells throughout adulthood. This occurs in a temporally controlled manner: an initial wave of HBC-derived neurogenesis was observed soon after birth, and a second wave of neurogenesis was observed at 4 months of age. Moreover, upon selective depletion of mature ORNs by olfactory bulbectomy, HBCs give rise to more neurons. Our findings demonstrate a crucial role for HBCs as multipotent progenitors in the adult OE, acting during normal neuronal turnover as well as in acute regeneration upon injury.